CRL Ubiquitin Ligases and DNA Damage Response - Jin, Jianping; Li, Ju-Mei (Frontiers in Oncology, 2012)
Cullin/RING ubiquitin ligases (CRL) comprise the largest subfamily of ubiquitin ligases and are involved in various biological processes. One of the main functions of CRLs is to regulate DNA damage response, a fundamental signaling cascade to maintain genome integrity. In this review, we will discuss the regulation of CRL ubiquitin ligases and their roles in control of DNA damage response.